The lumpiness of German exports and imports of goods - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2016)
This paper looks at a hitherto neglected extensive margin of international trade by investigating for the first time the frequency at which German exporters and importers trade a given good with a given country. Imports and exports show a high degree of lumpiness. In a given year about half of all firm-good-country combinations are recorded only once or twice for trade with EU-countries, and this is the case for more than 60 percent of all firm-goodcountry combinations in trade with non-EU countries. The frequency of recorded transactions tends to decline with an increase in the number of transactions per year. This is in accordance with the presence of per-shipment fixed costs that provide an incentive for trading firms to engage in cross-border transactions infrequently. Empirical models show that for Germany the frequency of transactions at the firm-good-country level tends to decrease with an increase in per-shipment costs when unobserved firm and goods characteristics are controlled for.
Keywords: F14; 330; lumpiness of trade; imports; exports; Germany